2018
DOI: 10.1177/1933719118804410
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Copy Number in Peripheral Blood in the First Trimester of Pregnancy and Different Preeclampsia Clinical Phenotypes Development: A Pilot Study

Abstract: Inflammation and oxidative stress are intrinsically linked to early poor placentation, typical of pregnancies complicated by preeclampsia associated with intrauterine growth restriction (PE-IUGR). Low mitochondrial DNA copy number (mtDNAcn) in peripheral blood constitutes a good peripheral surrogate marker of inflammation and oxidative stress. On these basis, we explored a possible correlation between mtDNAcn in peripheral blood in the first trimester of pregnancy and the PE-IUGR onset. To shed light on this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Our data demonstrate increases in the immunostimulatory potential of CFCmtDNA and upregulation of DNA degradation mechanisms in women with preeclampsia during the third trimester. Additionally, this study sets the foundation for future investigations in the exact role of CFCmtDNA in the pathogenesis of preeclampsia, as previous studies have suggested that CFCmtDNA may be a potential pathogenic trigger or a contributor to the maintenance of the maternal syndrome in preeclampsia 13, 15, 16 .…”
Section: Perspectivesmentioning
confidence: 80%
See 2 more Smart Citations
“…Our data demonstrate increases in the immunostimulatory potential of CFCmtDNA and upregulation of DNA degradation mechanisms in women with preeclampsia during the third trimester. Additionally, this study sets the foundation for future investigations in the exact role of CFCmtDNA in the pathogenesis of preeclampsia, as previous studies have suggested that CFCmtDNA may be a potential pathogenic trigger or a contributor to the maintenance of the maternal syndrome in preeclampsia 13, 15, 16 .…”
Section: Perspectivesmentioning
confidence: 80%
“…Cross-sectional and case-control studies have reported increased CFCmtDNA copy number in serum and whole blood from women with preeclampsia in the third trimester 13, 14 or at time of delivery 15 . On the other hand, CFCmtDNA was suppressed in the first trimester in women who later developed preeclampsia 16 . These previous studies suggest that CFCmtDNA may be a potential pathogenic trigger or a contributor to the maintenance of the maternal syndrome in preeclampsia.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Due to continuous apoptosis of placental trophoblasts, pregnancy can be viewed as a pseudoinflammatory state [ 22 ]. As a result, mtDNA is detectable in maternal plasma in normal pregnancy and increased in cases of many pregnancy complications [ 23 , 24 , 25 , 26 ]. This increases the interest of clinicians in cf-mtDNA fraction due to its potential application in diagnostics of pregnancy pathologies such as preterm birth that is known to be tightly connected with inflammation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced mtDNA copy number in patients with type 2 diabetes is now well evident ( Al-Kafaji et al, 2018 ; Fazzini et al, 2021 ; Latini et al, 2020 ; Xu et al, 2012 ). Busnelli et al (2019) ) demonstrated indirect relation between reduced mtDNA copy number and oxidative stress along with inflammation. Variants within mtDNA are population specific and are clustered in lineages that in turn define haplogroups.…”
Section: Introductionmentioning
confidence: 99%